Trade Book Reviews - Terri Sucio (Editor); Katie Caprino; Anita M. Dubroc; Ann Marie Smith (University of Oklahoma Libraries, 2022)
Are you looking for graphic novels to include in your classroom practice? YA scholars review: • When Stars are Scatterd by Victoria Jamieson and Omar Mohamed  • Banned Book Club by Kim Hyun Sook, Ko Hyun-Ju, and Ryan Estrada  • Seek You: A Journey Through American Loneliness by Kristen Radtke